Madagascar offers rare experience - Rolston, Holmes, 1932-2025, author; Fort Collins Coloradoan, publisher (Colorado State University. Libraries, 2010)
Rolston's account of a trip to Madagascar in October 2010. Lemurs, endemic fauna and flora, flying foxes, conservation in Madagascar, loss of biodiversity, forests, eroded landscape, poverty of Malagasy people.
Keywords: Madagascar forests; Madagascar degraded landscape; poverty in Madagascar; lemurs; Madagascar